Analysis and reflections on interactions in the accessibility portal - Malheiro, Cicera Aparecida Lima [UNESP]; Lima, Valeria Sperduti; Yanaze, Leandro Key Higuchi; Hollosi, Marcio (Univ Nove Julho, 2023)
The purpose of this article is to describe the concepts that underpinned the development of the Accessibility Portal at the Federal University of Sao Paulo (Unifesp). Through it, data on access and user interaction are presented, and reflections on its impact and contribution to the development of an inclusive culture in higher education are highlighted. The Portal was conceived within an investigative action through which an evaluation system composed of different tools and techniques was established, among which is Google Analytics. It was evident from the data how Portal users interacted in the available spaces and what are the main subjects of interest. It is noted that the contents addressed and the resources made available on the Portal are accessed worldwide, highlighting that inclusion and accessibility in higher education is a global demand.
Keywords: inclusion; university education; open education; accessibility